2012
DOI: 10.1177/0149206312443557
|View full text |Cite
|
Sign up to set email alerts
|

If You Wrong Us, Shall We Not Revenge? Moderating Roles of Self-Control and Perceived Aggressive Work Culture in Predicting Responses to Psychological Contract Breach

Abstract: Journal of Management / Month XXXX found that at high levels of perceived aggressive work culture, the conditional indirect effects of psychological contract violation in predicting workplace deviance via revenge cognitions were statistically significant for those employees with low as opposed to high self-control. These results were replicated in Sample 2 using an independent sample of 168 hospitality workers in a different cultural context. Overall, the results suggest that self-control and perceived aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 52 publications
3
118
0
1
Order By: Relevance
“…Numerous studies have demonstrated that not all responses to PCB are the same (Dulac et al, 2008;Ng et al, 2014), and the extent to which employees feel PCB is likely to be influenced by organizational and individual factors (Restubog et al, 2015). But the current research has not yet paid enough attention to the effects of organizational factors on the relationship between PCB and employees' reaction to it (Wang & Hsieh, 2014).…”
Section: Moderating Effect Of Perceived Hpwsmentioning
confidence: 86%
See 2 more Smart Citations
“…Numerous studies have demonstrated that not all responses to PCB are the same (Dulac et al, 2008;Ng et al, 2014), and the extent to which employees feel PCB is likely to be influenced by organizational and individual factors (Restubog et al, 2015). But the current research has not yet paid enough attention to the effects of organizational factors on the relationship between PCB and employees' reaction to it (Wang & Hsieh, 2014).…”
Section: Moderating Effect Of Perceived Hpwsmentioning
confidence: 86%
“…To minimize the negative effect of PCB, managers should pay more attention to understanding the organizational factors and individual characteristics that influence the employees' reaction to PCB (Restubog, Zagenczyk, Bordia, Bordia, & Chapman, 2015). At present, a considerable research has demonstrated that individuals may react differently to PCB, which might depend on individual characteristics, such as hostile attributional style (Chiu & Peng, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopt the reasoning of Bordia et al (2008), who suggest that psychological contract breach is an event that causes employees to experience an affective response (violation) that influences behavior and attitudes. In support of this view, Bordia et al (2008) and Restubog et al (2015) demonstrated a chain of events leading to workplace deviance: breach leads to violation, violation predicts revenge cognitions, and revenge cognitions predict deviant behavior. A number of other studies have shown that psychological contract violation mediates the relationship between psychological contract breach and outcomes (e.g., Turnley and Feldman, 1999; Kickul and Lester, 2001; Raja et al, 2004).…”
Section: Introductionmentioning
confidence: 85%
“…One's belief about another person's failure in fulfilling his/her obligations is termed psychological contract breach (Morrison and Robinson, 1997). The concept of psychological contract breach has been widely adopted for investigating employer-employee relationships (e.g., Deery et al, 2006;Lub et al, 2012;Restubog et al, 2012), because it is an essential factor in shaping employees' attitudes and behaviors (Aselage and Eisenberger, 2003). In the context of employee-customer relationship, customers possess certain expectations on the service delivery from service employees (Ariffin and Maghzi, 2012;Limpanitgul et al, 2013;Prayag and Ryan, 2012).…”
Section: Employee Incivility and Psychological Contract Breachmentioning
confidence: 99%